Pengaruh Berbagai Macam Pendinginan dan Pengemasan Terhadap Umur Simpan Jagung Manis (Zea mays saccharata) - Rustiningsih, Rustiningsih; Utama, Nafi Ananda; Rineksane, Innaka Ageng (Universitas Muhammadiyah Yogyakarta, 2005)
This research was aimed to study the influence of kinds of cooling and packing on the storage life of sweetcorn in order to obtain the simple postharvest technology and easy to practice. The research was done during the February - March of 2005 in the Research Laboratory of Agriculture Faculty, Muhammadiyah University of Yogyakarta. The reducing sugar analysis was done in the Agriculture Technology Faculty of Gadjah Mada University. The laboratory experiment was arranged ini 2 x 3 factorial completely randomized design with three replications. The cooling first factor was refrigerated in refrigerator to be compared to the hydro-cooling. Meanwhile, the polypropilene and polyethylene packaging were tested and compared to the unpackaged one. The flavor; reducing sugar, water content, percentage of nonconsumable part of sweetcorn, fresh weight of ears, and organoleptic properties were observed. The result showed that there was no significantly interaction between cooling and packaging on the storage life and quality of sweet corn. The cooling treatment was significantly influenced the starch and reducing sugar level as well as the packaging treatment. Refrigeration storage could significantly keep the level of reducing sugar to remain higher than the hydro-cooling, this treatment was also decreased the starch content, decreased the proportion of unconsumable part, and maintained the flavor. The polyethylene packaging significantly keep the level of reducing sugar to remain higher and relatively maintained the flavor than the polypropilene packaging or unpackaged, but decreased the portion of unconsumable part.